Efektifitas Variasi Media Semai Hidroponik Ramah Lingkungan dari Limbah Organik pada Tanaman Selada (Lactuca sativa L. - Jamallika, Sa'adah Nurwidyani; Salsabila, Aulia Rosada; Najichah, Dzakia Shofiatin; Rahmawati, Yunita Fera (Jurnal Agrotek Lestari, 2024)
The hydroponic technique is a solution for agricultural activities that do not require a large area of land because it does not require soil as a growing medium but uses water. Rockwool is a commonly used seedling medium in hydroponics. Organic waste has the potential to be used as seedling media because it contains many substances and microorganisms that are beneficial for plant growth. This study aimed to determine the effectiveness of banana fronds, sugarcane stalks, and orange peel waste as seedling media for lettuce (Lactuca sativa L.) plants that are environmentally friendly in hydroponics. This study used a Non-Factorial Completely Randomized Design (CRD) with five treatments and four replications, where each replication consisted of 20 samples. The results of DMRT analysis showed that various compositions and types of seedling media had different effects on each characteristic, namely seedling height, number of leaf blades, germination percentage, water absorption, and the level of consistency of the mash. Banana fronds, sugarcane stalks, and orange peel waste in the ratio of 1:2:1 have the potential to be an environmentally friendly seedling media for hydroponic lettuce cultivation.